Transformasi Genetik Tanaman Kentang (Solanum tuberosum L.) dengan Gen acvB Menggunakan Vektor Agrobacterium tumefaciens - DARWIN SILALAHI; I GEDE PUTU WIRAWAN; MADE SRITAMIN (Fakultas Pertanian Universitas Udayana, 2021)
Agrobacterium tumefaciens Mediated Genetic Transformation of acvB Gene in Potato (Solanum tuberosum L.). Genetic transformations are now routinely applied to plant mediated by Agrobacterium tumefaciens as the most convenient technique. This study aimed to prove the success of A. tumefaciens mediated genetic transformation in potato. A. tumefaciens LBA (pBI 121) and explant of potato shoot were used in this study. Explants were grown in vitro on Murashige and Skoog media. Transformation was implemented using smear technique by smearing A. tumefaciens to injured explant. Experimental groups consisted of two groups: control group which did not receive transformation treatment and treatment group receiving transformation treatment. Explant growth was observed through the presence of shoots, branches and the shoot height. Explants in the treatment group resulted in a higher number of shoots, branches, and shoot heights compared to control. Phenol compounds appear in explant epidermal tissue, indicating the wounds produced by A. tumefaciens infection, thus the gene predicted to be transformed. Identification by PCR is needed to prove the existence of the acvB gene in potato plants genome, using acvB specific PCR primer as the marker, such as (5?-CCCT CTAG AGAC CCGC GCCA AGGCG-3?) and (5?CGCG TCGA CCTT GTCG GAAAG -3?) with 540-bp in base pair size produced.